2019
DOI: 10.1002/2211-5463.12723
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 suppresses androgen synthesis in a mouse model of hyperandrogenism via IGF‐1 signaling

Abstract: Polycystic ovary syndrome (PCOS) is a major cause of anovulatory sterility in women, and most PCOS patients exhibit hyperandrogenism (HA). Liver kinase b1 (LKB1) is a tumor suppressor that has recently been reported to be involved in PCOS. However, the mechanism by which LKB1 affects HA has not previously been elucidated. We report here that ovarian LKB1 levels are significantly decreased in a female mouse model of HA. Moreover, we report that LKB1 expression is inhibited by elevated androgens via activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…An important role of AMPK-dependent mechanisms in the antiandrogenic action of MF in PCOS is supported by the data on the relationship between the androgen production and the activity of LKB1 in the ovaries of mice with experimental HA [ 199 ]. The LKB1 expression in the ovaries of hyperandrogenic mice is inhibited by high concentrations of androgens through activation of intracellular androgen receptors.…”
Section: Metformin and Polycystic Ovary Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…An important role of AMPK-dependent mechanisms in the antiandrogenic action of MF in PCOS is supported by the data on the relationship between the androgen production and the activity of LKB1 in the ovaries of mice with experimental HA [ 199 ]. The LKB1 expression in the ovaries of hyperandrogenic mice is inhibited by high concentrations of androgens through activation of intracellular androgen receptors.…”
Section: Metformin and Polycystic Ovary Syndromementioning
confidence: 99%
“…In opposite, LKB1 activation leads to a decrease in the androgens production by theca cells, but increases the estrogen production by granulosa cells. Transgenic mice overexpressing LKB1 are characterized by the increased resistance to the development of HA [ 199 ]. Mice with a functionally inactive ovarian gene Lkb1 have significantly enlarged ovaries and activated entire pool of primordial follicles, but without further maturation and ovulation, which results in the premature ovarian failure and severely reduced fertility [ 200 ].…”
Section: Metformin and Polycystic Ovary Syndromementioning
confidence: 99%
“…In another study, detailed research was carried on LKB1. It was observed that LKB1 has an inhibitory action on androgens in theca cells of the ovary, whereas the excess amount of androgens suppresses LKB1 activity [33]. This suggests a possible LKB1 link to PCOS disease.…”
Section: Genetics Of Pcos and Its Dermatological Manifestationsmentioning
confidence: 99%
“…IGFR is understood to have a negative impact on CYP17 and a positive one on CYP19. Thus, in PCOS, where androgen is on a higher level, there will be IGFR activity present and, consequently, high CYP19 and dysfunctioning CYP17 levels are recorded [33,34]. In a study among 198 Iranian patients diagnosed with acne vulgaris conducted to shed some light on the association between acne vulgaris and two genotypes of CYP 450 (CYP 17 and CYP 19), it was proved that both genotypes are connected to the occurrence of acne vulgaris [35].…”
Section: Genetics Of Pcos and Its Dermatological Manifestationsmentioning
confidence: 99%